PERANAN KYAI DALAM PENGEMBANGAN PENDIDIKAN FORMAL DI PESANTREN (Studi Kasus di Pesantren Darussalam Blokagung, Tegalsari, Banyuwangi) - Al Muftiyah (Jurnal Ilmiah Ar-Risalah: Media Ke-Islaman, Pendidikan dan Hukum Islam, 2013)
In the history of the oldest educational institutions inIndonesia is the school and the holder of the highest role in it wasa teacher of Islam. A religious scholars not only as a central pointof all activities at the school, but also as a religious teacher, acharacter, giving an example to all the people around him.Existence of Formal Education at Pesantren DarussalamBlokagung, in its management of education in the foundationPesantren Darussalam Blokagung is adhering to the maqolah"almuhafadhotu 'ala alqodiimi as-shoolih wa-al-akhdu bi-aljadiidial-aslah (keeping cases good old and taking new cases arebetter)". The development of education in schools DarussalamBlokagung Banyuwangi progressing very rapidly, since the start ofthis boarding establishment, starting with education diniyah untilmadrasah school education, junior seed, to college